Know Thyself - Beuscart, R. (Methods of Information in Medicine, 2013)
This article is part of a For-Discussion-Section of Methods of Information in Medicine on “Biomedical Informatics: We Are What We Publish” written by Peter L. Elkin, Steven H. Brown, and Graham Wright. It is introduced by this editorial and followed by a commentary paper with invited comments. In their paper, P. Elkin et al. attempt to define the fields of Medical Informatics and Bioinfor matics through a bottom-up approach by searching the medical literature. This innovative approach provides interesting results that are discussed in the commentary paper. In subsequent issues the discussion may continue through letters to the editor.
Keywords: Medical Informatics; Bioinformatics; e-Health